The Relationship between Peer Support and Academic Stress in High School SMA Negeri 6 Bulukumba Students - Pramudyanti, Yenilia Rezky; Alwi, Muh. Ahkam (Polteknik Ilmu Pemasyarakatan, 2024)
when students are faced with various obstacles and demands that can make them feel burdened and cause academic stress among students. This study aims to determine the relationship between peer support and academic stress in students of one of the high schools in Bulukumba Regency. The research method used is the quantitative method. Respondents in this study were 145 students of class XII of SMA Negeri 6 Bulukumba with an age range of 16 to 18 years. The results of this study indicate that there is a relationship between peer support and academic stress in students of class XII of SMA Negeri 6 Bulukumba with a value of (r = -264) and a significant value (p = 0.001). Therefore, H1 is accepted and H0 is rejected. The implications of this study are to provide information and references regarding the importance of peer support in reducing academic stress in high school students.